Fine structure of the ladybird spermatozoa (Insecta, Coleoptera, Coccinellidae). Issue 3 (May 2018) - Dallai, Romano; Lino-Neto, José; Dias, Glenda; Nere, Pedro H.A.; Mercati, David; Lupetti, Pietro
Abstract: The sperm structure of several ladybird species belonging to different subfamilies of Coccinellidae was studied. Three main sperm types were clearly recognized, and were characterized by differences in acrosomal length, the presence of a dense coat around the acrosome, the length of the basal body, the amount of the centriole adjunct material, and the diameter of the mitochondrial derivatives. However, the whole group shares a pattern of the posterior sperm region uncommon for insects, in which the axoneme and other flagellar components are running parallel with the nucleus. As a general conclusion, this study has revealed an inconsistency between the sperm structure and the systematics of the group, indicating that the generic concepts within the group do not reflect a natural classification, a statement also shared by molecular studies. Highlights: Ladybird spermatozoa have the atypical position of nucleus and axoneme that run in parallel along the posterior sperm region. Coccinellidae exhibit three different sperm types. The most common sperm type of Coccinellidae has a long acrosome and a long basal body.